Topical and systemic JAK inhibitors in hand eczema – a narrative review. (3rd April 2023) - Zalewski, Adam; Szepietowski, Jacek C.
ABSTRACT: Introduction: Hand eczema is a chronic inflammatory skin disease characterized by significant prevalence and impact on patients' Quality of Life (QoL). Because of its complex and diverse clinical picture, HE management requires patient-specific treatment which may constitute a challenge. First described in the 1990s, Janus kinase inhibitors (JAK inhibitors) state a group of modern therapeuticals, which exhibit good bioavailability and are well tolerated by patients in both – topical and systemic – routes of administration. They are an immunomodulating small molecules, impacting JAKs' enzymatic activity. Areas covered: This review provides a summary of available data concerning JAK inhibitors' use in HE patients, regarding also clinical trials for the HE treatment. Expert opinion: Recent studies are introducing JAK inhibitors as an alternative for other topical and systemic therapies in HE patients. Treatment targeting specific immune pathways enables precise management and extends range of potential therapeutic options. Despite early promising results, future studies need to evaluate JAK inhibitors' safety, potential risks and benefits resulting from the treatment, as well as impact of the therapy on patients' QoL.